Respiratory mycoplasmas - Gillespie, Stephen (Henry Stewart Talks, 2015)
Characteristics of mycoplasmas, Human mycoplasmas, M. pneumoniae: epidemiology, pathogenesis, infection syndromes, clinical features, complications and treatment, Diagnosis of infection, Growing mycoplasma, Newly discovered M. amphoriforme: identification, genomics and treatment, Future research